Measuring the Awareness and Acceptance level Innovative Learning Strategies of Higher Secondary School Teachers of Sindh, Pakistan - Rahoo, Liaquat Ali; Hasnain, Paras; Ahmed, Tanveer; Khan, Muhammad Ali; Asghar, Ali (The journal of contemporary issues in business and government, 2021)
Evolution of Information and communication technology in the last few decades, has revamped the Education System. Traditional learning alone can no longer meet the needs of the learner or neither prepares them to survive in the 21st century knowledge and technology based society. The aim of this study is to know the awareness and acceptance level of innovative strategies of teachers: A case study of Hyderabad Division. Innovative teaching strategies help the students to understand the content in different dimensions. It provides the platform to students for varied experiences and responses. The present study focuses on the awareness and acceptance of innovative teaching learning strategies in teachers of higher secondary schools.The study used primary data sources from teachers of colleges at Hyderabad which included field notes and semi-structured interviews. Questionnaire which consists two parts: Part A: Acceptance of innovative teaching learning strategies Part B: Awareness of innovative teaching learning strategies. The population of the study was Hyderabad district. The simple random sampling technique was used for data collection. The sample size of the study was 200 teachers from various colleges of Hyderabad District. SPSS software was used for data analysis which include statistical methods descriptive and Inferential.The study reveals innovative strategies are more used by B.Ed. teacher trainee than B.Sc.teachers. Teachers of science stream are taking more interest than Arts stream. The innovative strategies are more practical in male than female.